Extending the MOISE model with adjustable autonomy - Maia, Artur Vidal; Sichman, Jaime Simão (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC), 2017)
Having autonomy and being part of an organization can be opposite concepts. Autonomy lets an agent take his own decisions, while sometimes, being part of an organization constraints these decisions to the ones allowed by the organization. This works presents an idea to combine these aspects, by allowing an agent to have autonomy even if it take part of an organization. We present different types of roles and goals to tackle this problem, characterizing what is called adjustable autonomy.